Accommodation Facilities in Temajuk as Border Areas of Indonesia: A Preliminary Study - Rosalina, Tita; Evita, Rossi; Pranoto, Setya Aristu; Mutiaraningrum, Ira (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The large number of tourists visiting Temajuk Village is supported by local people's initiatives to start businesses in accommodation, including lodging, resorts, and homestays. This study examined accommodation facilities in supporting the development of Temajuk Tourism Village, West Kalimantan, Indonesia. This study explored the physical, environmental, and social components of accommodation that support tourism. The study identified the availability of lodging, resorts, and homestays, as well as facilities and amenities in the village. Data collection was carried out through questionnaires, observations, and interviews. Questionnaires were distributed to the managers of lodging, resorts, and homestays. Semi-structured interviews were also conducted with the accommodation managers in the Temajuk Tourism Village. The data analysis technique refers to the explanation of descriptive quantitative with percentages for questionnaires and elaboration of interview results and the observation results. Since there has been no study giving data on accommodation in Temajuk, this study will enrich the literature as well as help other researchers in the future writing about Temajuk Village.